Towards a Taxonomy of Textual Entailments - Przepiórkowski, Adam; Kozakoszczak, Jakub; Winkowski, Jan; Ziembicki, Daniel; Teleżyński, Tadeusz (Proceedings of the Amsterdam Colloquium, 2015)
This paper reports on work in progress which aims at the creation of a comprehensive taxonomy of textual entailment rules and– as a proof of concept– its application to an RTE corpus. In particular, a new formalism for encoding entailment rules is proposed, with some emphasis on encoding the properties of such rules and their converses in different polarity contexts.